Cross-Talk Between Iron and Glucose Metabolism in the Establishment of Disease Tolerance - Carlos, Ana Rita; Weis, Sebastian; Soares, Miguel P. (Frontiers in Immunology, 2018)
Infectious diseases are associated with disruption of host homeostasis. This can be triggered directly by pathogens or indirectly by host immune-driven resistance mechanisms. Disease tolerance is a defense strategy against infection that sustains host homeostasis, without exerting a direct negative impact on pathogens. The mechanisms governing disease tolerance encompass host metabolic responses that maintain vital homeostatic parameters within a range compatible with survival. Central to this defense strategy is the host´s ability to sense and adapt to variations in nutrients, such as iron and glucose. Here we address how host responses regulating iron and glucose metabolism interact to establish disease tolerance and possibly modulate resistance to infection.